Hepatitis B virus infection: Epidemiology and seroprevalence rate amongst negrito tribe in Malaysia - Sahlan, Noraziah; Nor, Fadhilah Mohd; Muslim, Azdayanti; Shaari, Syahrul Azlin; Rahman, Thuhairah Hasrah Abdul; Hoh, Boon Peng (Malaysian Medical Association, 2019)
Introduction: Prevalence of Hepatitis B virus (HBV) infection among the non-indigenous people in Malaysia has been well established and range between 3% and 5%. However, data from the indigenous (Orang Asli) people is still lacking. The Negrito population is the most remotely located Orang Asli tribe with limited access to health care facilities. This study was undertaken to determine the epidemiology and seroprevalence of HBV infection among the Negrito. Methods: Surveys were conducted in five Negrito settlements in Kelantan and Perak states in Malaysia. A total of 150 participants were recruited. Clinical history was taken and physical examination was performed. Five millilitres of whole blood were collected and tested for hepatitis B surface antigen (HBsAg) using electrochemiluminescence immunoassay. Results: Participants were mainly from the Bateq (49.3%) and Mendriq (29.4%) sub-tribes. Overall, 13 subjects (8.7 %); nine males and four females were HBsAg positive. Nine of the HBsAg positive subjects were ≥35 years old. All of them had history of home deliver without evidence of antenatal record. Six (46%) of the HBsAg positive subjects had tattoo and body piercing in the past. Conclusion: The prevalence of HBV infection rate amongst the Negrito tribe is almost three-fold compared to the national rates. The reason for this finding remains unclear. Tattooing, body piercing and vertical transmission could be the main possible routes of transmission of HBV among the Negrito population in Malaysia. © 2019, Malaysian Medical Association. All rights reserved.